An Evaluation of Neurosurgical Resident Education and Sentiment During the COVID-19 Pandemic: A North American Survey. (16th November 2020) - Pelargos, Panayiotis E; Zhao, Yan; Smith, Zachary A; Dunn, Ian F; Bauer, Andrew M
Abstract: INTRODUCTION: Restrictions in elective surgery and large group gatherings as well as changes in faculty and resident schedules during the COVID-19 pandemic has led to rapid evolvement of the training curriculum for neurosurgical trainees. While necessary, these changes may have significant impact on the training of neurosurgery residents. METHODS: A survey assessing changes to resident clinical and educational workload and their sentiment about how these changes may affect their careers was distributed electronically to neurosurgery residents in the United States and Canada. RESULTS: One hundred ninety-seven resident responses were collected between April 17, 2020 and April 30, 2020. The survey respondents were spread over 29 states and Canada and were evenly spread across all residency levels ( P = .619). Nearly 82% reported that the inpatient and outpatient volumes were either greatly (44.0%) or moderately (37.8%) reduced. Greater than 91% reported a significant reduction in work hours and a significant increase in resident didactics ( P < .001). Nearly all residents surveyed (98.5%) reported that their program had converted to electronic platforms for their didactic lectures, and there was a significant increase in the time residents spent in didactic lectures. Residents reported converting the majority of their time outside of neurosurgery clinical responsibilities into watching remote didactic lectures, conducting research, and preparing for board examinations, while nearly 14% of trainees spent at least a portion of that time providing COVID-19 medical care. Senior residents were more likely to express concern about their educational experience as well as their future career prospects. CONCLUSION: Universally, residents have experienced reduced work hours and operative case volumes. Programs have adapted by increasing didactic time and using electronic platforms. The findings suggest that senior residents may feel the effects more than their junior counterparts. This may require more acute attention from faculty with respect to preparing senior residents for moving on to fellowship or ultimate job. It is possible that this remarkable time period will prompt a critical re-appraisal of the pre-COVID-19 adequacy of educational content in our training programs, and that enhanced educational efforts driven by this pandemic may be lasting.